How to prove this identity? $$\pi=\sum_{k=-\infty}^{\infty}\left(\dfrac{\sin(k)}{k}\right)^{2}\;$$ I found the above interesting identity in the book $\bf \pi$ Unleashed.

Does anyone knows how to prove it?


  • 18
    $\begingroup$ Just for clarification, what happens when $k=0?$ $\endgroup$
    – L. F.
    Mar 15 '13 at 17:52
  • 2
    $\begingroup$ For more fun along these lines, see web.cs.dal.ca/~jborwein/sinc-sums.pdf $\endgroup$
    – user940
    Mar 15 '13 at 17:58
  • 2
    $\begingroup$ @L.F. at $k=0$, the limit is taken leading to $1$. See Ron's answer below. $\endgroup$
    – nbubis
    Mar 15 '13 at 18:16
  • $\begingroup$ A related problem. $\endgroup$ Mar 19 '13 at 13:42

Find a function whose Fourier coefficients are $\sin{k}/k$. Then evaluate the integral of the square of that function.

To wit, let

$$f(x) = \begin{cases} \pi & |x|<1\\0&|x|>1 \end{cases}$$

Then, if

$$f(x) = \sum_{k=-\infty}^{\infty} c_k e^{i k x}$$


$$c_k = \frac{1}{2 \pi} \int_{-\pi}^{\pi} dx \: f(x) e^{i k x} = \frac{\sin{k}}{k}$$

By Parseval's Theorem:

$$\sum_{k=-\infty}^{\infty} \frac{\sin^2{k}}{k^2} = \frac{1}{2 \pi} \int_{-\pi}^{\pi} dx \: |f(x)|^2 = \frac{1}{2 \pi} \int_{-1}^{1} dx \: \pi^2 = \pi $$


This result is easily generalizable to

$$\sum_{k=-\infty}^{\infty} \frac{\sin^2{a k}}{k^2} = \pi\, a$$

where $a \in[0,\pi)$, using the function

$$f(x) = \begin{cases} \pi & |x|<a\\0&|x|>a \end{cases}$$

  • 6
    $\begingroup$ On the Wolfram MathWorld web page for the sinc function it states, "The remarkable fact that the sums of $\text{sinc}(k)$ and $\text{sinc}^{2}(k)$ are equal appears to have first been published in Baillie (1978)." I remember reading that a long time ago and thinking that summing $\text{sinc}^{2}(k)$ must be really difficult if no one realized they were the same until 1978. But the evaluation is mostly straightforward as you showed. Strange. $\endgroup$ Mar 15 '13 at 18:56
  • 1
    $\begingroup$ @RandomVariable: Huh, how odd. Interesting find. (+1) $\endgroup$
    – Ron Gordon
    Mar 15 '13 at 19:13
  • 2
    $\begingroup$ I accidentally plugged $\sum _{k=-\infty }^{\infty } \frac{\sin (k)}{k}$ (without the square) into Mathematica and it also gave $\pi$. I wonder why this identity with the square is the common one. The evaluation of this sum to the first few powers are: $\left\{\pi ,\pi ,\frac{3 \pi }{4},\frac{2 \pi }{3},\frac{115 \pi }{192},\frac{11 \pi }{20}\right\}$ (in case you see these on Jeapardy). The seventh power evaluates to $\frac{129423 \pi -201684 \pi ^2+144060 \pi ^3-54880 \pi ^4+11760 \pi ^5-1344 \pi ^6+64 \pi ^7}{23040}$ and the subsequent powers are all complicated-looking like this. $\endgroup$
    – amr
    Mar 16 '13 at 20:26
  • 1
    $\begingroup$ @amr: see the reference that Random provided. It is kind of interesting that the sum over sinc equals this sum. I'd like to see it derived as something other than a coincidence. Interesting also about the seventh power thing. Even powers of sinc may be summed using Parseval similar to how I outline above. $\endgroup$
    – Ron Gordon
    Mar 16 '13 at 20:30
  • 1
    $\begingroup$ @amr This discussion here was very helpful for me in this topic which you might wish to see: mathematica.stackexchange.com/questions/157444/… $\endgroup$ Oct 10 '17 at 15:54

Assume $a\in\left[0,\frac\pi2\right]$.

An integral $$ \begin{align} \int_0^a\frac{\sin(2kx)}{k}\mathrm{d}x &=\int_0^a\frac{2\sin(kx)}{k^2}\mathrm{d}\sin(kx)\\ &=\left.\frac{\sin^2(kx)}{k^2}\right]_0^a\\ &=\frac{\sin^2(ka)}{k^2}\tag{1} \end{align} $$ and a sum $$ \begin{align} \sum_{k=1}^\infty\frac{\sin(2kx)}{k} &=\sum_{k=1}^\infty\frac{e^{i2kx}-e^{-i2kx}}{2ik}\\ &=\frac1{2i}\left(-\log(1-e^{i2x})+\log(1-e^{-i2x})\right)\\ &=\frac1{2i}\log(-e^{-i2x})\\[4pt] &=\frac\pi2-x\quad\text{for }x\in\left(0,\pi\right)\tag{2} \end{align} $$ Putting $(1)$ and $(2)$ together $$ \begin{align} \sum_{k=1}^\infty\frac{\sin^2(ka)}{k^2} &=\int_0^a\left(\frac\pi2-x\right)\,\mathrm{d}x\\ &=\frac\pi2a-\frac{a^2}2\tag{3} \end{align} $$ If we take $\dfrac{\sin(ka)}{ka}=1$ when $k=0$, we get the answer to the question using $a=1$: $$ \sum_{k\in\mathbb{Z}}\left(\frac{\sin(ka)}{ka}\right)^2=\frac\pi a\tag{4} $$

Application to a Riemann Sum

If we multiply $(4)$ by $a$ and set $a=\frac1n$, we get $$ \sum_{k\in\mathbb{Z}}\frac{\sin^2(k/n)}{(k/n)^2}\frac1n=\pi\tag{5} $$ $(5)$ is a Riemann sum which shows that $$ \int_{-\infty}^\infty\frac{\sin^2(x)}{x^2}\,\mathrm{d}x=\pi\tag{6} $$

First Power of Sinc

We can also use $(2)$ at $x=\frac a2$, assuming $\frac{\sin(ka)}{ka}=1$ when $k=0$, to get $$ \sum_{k\in\mathbb{Z}}\frac{\sin(ka)}{ka}=\frac\pi a\tag{7} $$ Again, multiplying $(7)$ by $a$ and letting $a=\frac1n$, we get $$ \sum_{k\in\mathbb{Z}}\frac{\sin(k/n)}{k/n}\frac1n=\pi\tag{8} $$ and $(8)$ is a Riemann sum which shows that $$ \int_{-\infty}^\infty\frac{\sin(x)}{x}\,\mathrm{d}x=\pi\tag{9} $$

  • $\begingroup$ Interesting approach (+1). How easily does it generalize to other sums of powers of sincs? $\endgroup$
    – Ron Gordon
    Mar 23 '13 at 8:52
  • $\begingroup$ @RonGordon: I noticed that $(2)$ gives the result for the first power of sinc, and then noticed that these results apply to Riemann sums. I will look into higher powers. $\endgroup$
    – robjohn
    Mar 23 '13 at 12:15
  • $\begingroup$ Very nifty! I'd upvote you again, but...well, you know. Anyway, that's a really important observation and may also help add more insight into a question I answered yesterday about the link between Fourier transforms and Fourier series. $\endgroup$
    – Ron Gordon
    Mar 23 '13 at 12:18
  • $\begingroup$ This is that question to which I referred: math.stackexchange.com/questions/329576/… $\endgroup$
    – Ron Gordon
    Mar 23 '13 at 13:14
  • $\begingroup$ @RonGordon: I generalized this to third powers in this answer. $\endgroup$
    – robjohn
    Jul 27 '13 at 14:35

I'll try to tackle the sum for general powers of $\operatorname{sinc}{x}$. It seems that the general formula is $$ \begin{align} \sum_{m = -\infty}^\infty& \left(\frac{\sin{(m)}}{m}\right)^n \tag{0}\\ & = \frac{(-1)^{n}\pi}{2^{n}(n-1)!}\sum_{\ell = -\lfloor n/(2\pi)\rfloor}^{\lfloor n/(2\pi)\rfloor}\left(\sum_{k = 0}^n(-1)^k{n\choose k} (2\pi \ell - n+2k)^{n-1}\operatorname{sign}(2\pi \ell-n+2k)\right). \end{align} $$

Before I get into that, I'm going to give another solution to the problem posed originally in the question. I'll use the Poisson summation formula, namely, $$ \sum_{n = -\infty}^\infty f(x+n) = \sum_{\ell = -\infty}^\infty \hat{f}(2\pi \ell) e^{2\pi i \ell x}. $$ Here $f$ is a function with reasonable regularity and decay properties, and $$ \hat{f}(t) = \int_{-\infty}^\infty f(x)e^{-itx}\,dx $$ is the Fourier transform of $f$. The idea is of course to take take $f(x) = \operatorname{sinc}^2{x}$.

I'm going to start by proving directly that $$ \begin{align} \int_{-\infty}^\infty (\operatorname{sinc}{x})^2e^{-itx}\,dx = \int_{-\infty}^\infty \left(\frac{\sin{x}}{x}\right)^2e^{-itx}\,dx = \frac{\pi}{4}(|x-2| + |x+2| - 2|x|). \tag{1} \end{align} $$ The right hand side is just a concise expression (that happens to be suggestive of the general situation) for the triangle-shaped function that is $\pi(1-|x|/2)$ when $|x| < 2$ and $0$ otherwise. An application of the Poisson summation formula referenced above then gives $$ \sum_{n = - \infty}^\infty \left(\frac{\sin{(x+n)}}{x+n}\right)^2 = \pi, $$ for all $x \in \mathbb{R}$. Taking $x = 0$ will give the result you seek.

To prove the identity $(1)$, write $$ \operatorname{sinc}{x} = \frac{\sin{x}}{x} = \frac{1}{2}\int_{-1}^1 e^{-ixt}\,dt = \hat{g}(x), $$ where $g = (1/2)\chi_{[-1,1]}$ is one half times the characteristic function of the interval $[-1,1]$. The Fourier transform converts convolution to multiplication, so $$ \widehat{g*g}(x) = \left(\frac{\sin{x}}{x}\right)^2. $$ The right-hand side (the square of $\operatorname{sinc}{x}$) is integrable, so an application of the Fourier inversion formula gives us $$ \int_{-\infty}^\infty \left(\frac{\sin{x}}{x}\right)^2e^{itx}\,dx = 2\pi (g*g)(t) = \frac{\pi}{2}\int_{-\infty}^\infty \chi_{[-1,1]}(t-y)\chi_{[-1,1]}(y)\,dy. $$ The evaluation of the integral on the right is straightforward (but a little tedious), and it gives us $(1)$.

The method just used to prove the identity $(1)$ has the benefit of being elementary, and does generalize to higher powers of $\operatorname{sinc}{x}$ (in the sense that $(-1)^n2\pi$ times the $n$-fold convolution of $(1/2)\chi_{[-1,1]}$ with itself is the Fourier transform of $\operatorname{sinc}{x}$ raised to the $n$th power) but unfortunately the computations become quite involved. Thus, I'll use another method, one that requires some basic knowledge of distribution theory, to prove—for positive integers $n$—that $$ \begin{align} \widehat{\operatorname{sinc}^n}{(x)} &= \int_{-\infty}^\infty \left(\frac{\sin{t}}{t}\right)^ne^{-ixt}\,dt \\ & = \frac{(-1)^n\pi}{2^{n}(n-1)!}\sum_{k = 0}^n(-1)^k{n\choose k} (x - n+2k)^{n-1}\operatorname{sign}(x-n+2k). \tag{2} \end{align} $$ Applying the Poisson summation formula to this identity leads to $(0)$—almost. I still have to explain why the upper and lower bounds of summation in the right hand side of $(0)$ are finite, which I'll do now. Since $(2)$ is equal to a constant multiple of the $n$-fold composition of $\chi_{[-1,1]}$ with itself, it is supported in $[-n,n]$. (This can also be seen directly.) Therefore, in the right hand side of the Poisson summation formula, we need only sum over those indices $\ell$ satisfying $|\ell|<n/2\pi$. This is where the upper and lower bounds come from in the equation $(0)$.

So all that remains is to prove the equation $(2)$. Let me briefly outline the tools we'll need. Let $\mathscr{S} = \mathscr{S}(\mathbb{R})$ denote the Schwartz space on $\mathbb{R}$. Let $u_n : \mathscr{S} \to \mathbb R$ be the distribution defined for $\varphi \in \mathscr{S}$ by $$ u_n(\varphi) = \lim_{\epsilon \to 0^+}\int_{|x|>\epsilon} \frac{\varphi(x) - \sum_{k=0}^{n-2}\varphi^{(k)}(0)x^k/k!}{x^n}\,dx. $$ Basically, $u_n$ is the distribution best resembling the function $x^{-n}$. In fact, if $h$ is a smooth function that vanishes to order $n$ at the origin, then the distribution $h\cdot u_n$ is equal to the function $h(x)/x^n$. As one would expect from the relation $\partial^k x^{-1} = (-1)^{k}k! x^{-k-1}$, the $k$th distributional derivative of $u_1$ is given by $\partial^ku_1 = (-1)^kk!\, u_{k+1}$. This is all proved straightforwardly.

It turns out that $$ \hat{u}_1(t) = -i\pi \operatorname{sign}(t), $$ where $\operatorname{sign}(t)$ is the usual sign function that returns $0$ when $t = 0$ and $t/|t|$ otherwise. (This can be proved by regarding $\operatorname{sign}(t)$ as a limit $\lim_{k\to \infty} \chi_{(0,k]}(t) - \chi_{[-k,0)}(t)$, taking the distributional limit of the Fourier transforms, and then applying the inverse Fourier transform.) Now, for any distribution $v$, one has $$ \widehat{\partial^k v} = (it)^k \hat{v}. $$ Thus, using $u_n = (-1)^{n-1}(n-1)!^{-1}\partial^{n-1} u_1$, $$ \hat{u}_n(t) = \frac{(-1)^{n-1}}{(n-1)!}\widehat{\partial^n u_1}(t) = \frac{(-1)^{n-1}}{(n-1)!}(it)^{n-1}\hat{u}_1(t) = \frac{(-1)^{n}i^n\pi}{(n-1)!}t^{n-1} \operatorname{sign}(t). \tag{3} $$ Finally, another property of the Fourier transform dictates that $$ \widehat{e^{ihx}u_n}(t) = \hat{u}_n(x-h). \tag{4} $$ We're now prepared to evaluate the Fourier transform of $(\operatorname{sinc}{x})^n$.

Since $(\sin{x})^n$ vanishes to order $n$ at the origin, we have $$ (\operatorname{sinc}{x})^n = (\sin{x})^n x^{-n} = (\sin{x})^nu_n $$ as distributions. If we now expand $(\sin{x})^n$ into powers of $e^{ix}$, we get $$ (\sin{x})^nu_n = \frac{1}{(2i)^n} \sum_{k = 0}^n(-1)^k{n\choose k}e^{i(n-2k)x}u_n. $$ Taking the term-wise Fourier transform of the right hand side and inserting the formulas $(3)$ and $(4)$, we arrive at $$ \begin{align} \widehat{\operatorname{sinc}^n}\,(t) &= \frac{1}{(2i)^n} \sum_{k = 0}^n(-1)^k{n\choose k}\widehat{e^{i(n-2k)x}u_n}(t) \\ & = \frac{1}{(2i)^n} \sum_{k = 0}^n(-1)^k{n\choose k}\hat{u}_n(t-n+2k)\\ & = \frac{1}{(2i)^n} \sum_{k = 0}^n(-1)^k{n\choose k}\frac{(-1)^{n}i^n\pi}{(n-1)!}(t-n+2k)^{n-1}\operatorname{sign}(t-n+2k). \end{align} $$ Simplifying then gives $(2)$.

  • $\begingroup$ In your equation (1), are you integrating over $x$ or $t$? You integrate over $x$ in the LHS but have a function of $x$ in the RHS. $\endgroup$ May 27 '16 at 4:04

This sum may be calculated by computing a Mellin transform of a suitable function and then inverting that to get the sum. First start by rearranging some terms, so that the target sum $S$ becomes $$ S = 1 + 2 \sum_{k\ge 1} \frac{\sin(k)^2}{k^2}.$$ Now introduce $$ f(x) = \sum_{k\ge 1} \frac{\sin(xk)^2}{k^2}$$ so that we are looking for $f(1).$ Rewrite $f(x)$ as follows: $$ f(x) = - \frac{1}{4} \sum_{k\ge 1} \frac{e^{2ixk}-2+e^{-2ixk}}{k^2} = \frac{1}{2}\sum_{k\ge 1} \frac{1}{k^2} - \frac{1}{4} \sum_{k\ge 1} \frac{e^{2ixk}+e^{-2ixk}}{k^2} \\= \frac{\pi^2}{12} - \frac{1}{4} \sum_{k\ge 1} \frac{e^{2ixk}+e^{-2ixk}}{k^2}.$$ Using Mellin transforms, we find $$\mathfrak{M}\left(\sum_{k\ge 1}\frac{e^{2ixk}}{k^2};s\right)= \Gamma(s) \sum_{k\ge 1} \frac{1}{(2ik)^s k^2} = \frac{1}{(2i)^s}\Gamma(s) \zeta(s+2).$$ Similarly, $$\mathfrak{M}\left(\sum_{k\ge 1}\frac{e^{-2ixk}}{k^2};s\right)= \Gamma(s) \sum_{k\ge 1} \frac{1}{(-2ik)^s k^2} = \frac{1}{(-2i)^s}\Gamma(s) \zeta(s+2).$$ Now observe that $$ \frac{1}{(2i)^s} + \frac{1}{(-2i)^s} = e^{-s \log(2i)} + e^{-s \log(-2i)} = e^{-s \log 2 -s i\pi/2} + e^{-s \log 2 + s i\pi/2} \\ = 2^{-s} 2 \cos(s\pi/2)$$ Putting these two together, we obtain $$ \mathfrak{M}\left(\sum_{k\ge 1}\frac{e^{2ixk}+e^{-2ixk}}{k^2};s\right) = g^*(s)= 2 \times 2^{-s} \cos(s\pi/2) \Gamma(s) \zeta(s+2).$$ We will apply Mellin inversion to this term. There is a pole from the zeta and gamma functions at $s=-1$ (which the cosine turns from a double into a single pole) and one from the gamma function at $s=0$ and another one from the gamma function at $s=-2.$ The cosine term cancels the remaining poles of the gamma term at negative odd integers and the zeta term the ones at even integers. We have $$ \operatorname{Res}(g^*(s)x^{-s}; s=0) = \frac{\pi^2}{3},$$ $$ \operatorname{Res}(g^*(s)x^{-s}; s=-1) = -2\pi x,$$ $$ \operatorname{Res}(g^*(s)x^{-s}; s=-2) = 2 x^2.$$ This yields for the Mellin inversion integral that $$ \mathfrak{M}^{-1}(g^*(s);x) = \int_{1-i\infty}^{1+i\infty} g^*(s) x^{-s} ds = 2 x^2 - 2\pi x + \frac{\pi^2}{3}.$$ Returning to $S$ we have shown that $$S = 1 + 2\left(\frac{\pi^2}{12}-\frac{1}{4} \left( 2-2\pi + \frac{\pi^2}{3}\right) \right) = 1 - \frac{1}{2} (2-2\pi) =\pi. $$

Remark, Feb 29 2020. It is proved at the following MSE link that the contribution from the left vertical line segment $\sigma \pm i\infty$ vanishes as we left-shift to $\sigma=-\infty$ when $x\in (0,\pi).$


There is a simple way to compute the sum. Note $$ \sum_{k=-\infty}^\infty\frac{\sin^2k}{k^2}=1+2\sum_{k=1}^\infty \frac{\sin^2k}{k^2}=1+\sum_{k=1}^\infty\frac{1-\cos(2k)}{k^2}=1+\frac{\pi^2}{6}-\sum_{k=1}^\infty\frac{\cos(2k)}{k^2}.$$ Letting $x=e^{2\theta i}$ in $\sum_{k=1}^\infty\frac{x^k}{k}=-\ln(1-x)$ gives us $$ \sum_{k=1}^\infty\frac{1}{k}(\cos(2k\theta)+i\sin(2k\theta))=-\ln(1-\cos(2\theta)-i\sin(2\theta)). $$ So $$ \sum_{k=1}^\infty\frac{1}{k}\sin(2k\theta)=-\Im\ln(1-\cos(2\theta)-i\sin(2\theta))=-\arctan(-\cot \theta)=\frac{\pi}{2}-\theta. $$ Integrating this derives $$ -\sum_{k=1}^\infty\frac{1}{2k^2}\cos(2k\theta)=\frac{\pi}{2}\theta-\frac{1}{2}\theta^2+C. $$ Letting $\theta=0$, we have $C=-\frac{\pi^2}{12}$. Thus $$ \sum_{k=1}^\infty\frac{1}{k^2}\cos(2k\theta)=-\pi \theta+\theta^2+\frac{\pi^2}{6}. $$ Letting $\theta=1$, we have $$ \sum_{k=1}^\infty\frac{\cos(2k)}{k^2}=-\pi+1+\frac{\pi^2}{6} $$ and hence $$ \sum_{k=-\infty}^\infty\frac{\sin^2k}{k^2}=1+\frac{\pi^2}{6}-\sum_{k=1}^\infty\frac{\cos(2k)}{k^2}=1+\frac{\pi^2}{6}-(-\pi+1+\frac{\pi^2}{6})=\pi.$$ It is easy to use the same trick to generalize this result to $\sum_{k=-\infty}^\infty\frac{\sin^2(ak)}{k^2}$. I omit the detail.


$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,}% \newcommand{\dd}{{\rm d}}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\half}{{1 \over 2}}% \newcommand{\ic}{{\rm i}}% \newcommand{\imp}{\Longrightarrow}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\ol}[1]{\overline{#1}}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}% \newcommand{\yy}{\Longleftrightarrow}$ $$ \!\!\!\!\!\sum_{k=-\infty}^{\infty}{\sin^{2}\pars{k} \over k^{2}} = \sum_{k=-\infty}^{\infty}\int_{-\infty}^{\infty}{\sin^{2}\pars{x} \over x^{2}}\, \delta\pars{x - k}\,\dd x = \int_{-\infty}^{\infty}{\sin^{2}\pars{x} \over x^{2}} \bracks{\sum_{k=-\infty}^{\infty}\delta\pars{x - k}}\,\dd x\tag{1} $$

The sum over $k$ in the right hand side of $\pars{1}$ is a periodic function of $x$ with period $1$ and it can be rewritten as follows: $$ \sum_{k=-\infty}^{\infty}\delta\pars{x - k} = \sum_{n = -\infty}^{\infty}a_{n}\expo{2n\pi\ic x}\tag{2} $$ The set of coefficients $\braces{a_{n}\ \ni\ n \in {\mathbb Z}}$ are given by: $$ 1 = \int_{-1/2}^{1/2}\expo{-2m\pi\ic x}\sum_{k=-\infty}^{\infty} \delta\pars{x - k}\,\dd x = \sum_{n = -\infty}^{\infty}a_{n}\int_{-1/2}^{1/2}\expo{2\pars{n - m}\pi\ic x}\,\dd x = a_{m} $$ which yields $\pars{~\mbox{see expression}\ \pars{2}~}$: $$ \sum_{k=-\infty}^{\infty}\delta\pars{x - k} = \sum_{n=-\infty}^{\infty}\expo{2n\pi\ic x}\tag{3} $$

We replace $\pars{3}$ in the right hand side of $\pars{1}$ to get: \begin{align} &\color{#0000ff}{\large\sum_{k=-\infty}^{\infty}{\sin^{2}\pars{k} \over k^{2}}} = \int_{-\infty}^{\infty}{\sin^{2}\pars{x} \over x^{2}} \sum_{n=-\infty}^{\infty}\expo{2n\pi\ic x}\,\dd x \\[3mm]&= \sum_{n=-\infty}^{\infty}\int_{-\infty}^{\infty} \pars{\half\int_{-1}^{1}\expo{\ic tx}\,\dd t} \pars{\half\int_{-1}^{1}\expo{\ic t'x}\,\dd t'} \expo{2n\pi\ic x}\,\dd x\tag{4} \\[3mm]&= {\pi \over 2}\sum_{n=-\infty}^{\infty} \int_{-1}^{1}\dd t\int_{-1}^{1}\dd t'\int_{-\infty}^{\infty}\expo{\pars{t + t' + 2n\pi}\ic x}\, {\dd x \over 2\pi} \\[3mm]&= {\pi \over 2}\sum_{n=-\infty}^{\infty} \int_{-1}^{1}\dd t\int_{-1}^{1}\dd t'\delta\pars{t + t' + 2n\pi} \\[3mm]&= {\pi \over 2}\sum_{n=-\infty}^{\infty} \int_{-1}^{1}\Theta\pars{1 - \verts{-t - 2n\pi}}\,\dd t = {\pi \over 2}\sum_{n=-\infty}^{\infty}\overbrace{\left.\int_{-1}^{1}\dd t \right\vert_{-1 - 2n\pi\ <\ t\ <\ 1 - 2n\pi}}^{\ds{=\ 2\,\delta_{n0}}} = \color{#0000ff}{\Large\pi} \end{align} where we use the identity $\ds{{\sin\pars{x} \over x} = \half\int_{-1}^{1}\expo{\ic tx}\,\dd t}.\quad$ See line $\pars{4}$.


This is a great place to apply Abel-Plana's formula

$$\sum_{n\geqslant 0} f(n)=\int_0^\infty f(x)\, dx+\frac{f(0)}{2}+i\int_0^\infty\frac{f(ix)-f(-ix)}{e^{2\pi x}-1}\, dx$$

Allow $f(x)=\left(\frac{\sin x}{x}\right)^2$

We note that, with the fact that $f$ is even $$\sum_{n\geqslant 0} \left(\frac{\sin n}{n}\right)^2=\frac{1}{2}\left(\sum_{n\in\Bbb{Z}}\left(\frac{\sin n}{n}\right)^2-1\right)$$

We already know that $$\int_0^\infty \left(\frac{\sin x}{x}\right)^2\, dx=\frac{\pi}{2};$$ and $$\frac{\sin 0}{0}:=1$$

Also, we easily determine that:$$\left(\frac{\sin ix}{ix}\right)^2=\left(\frac{\sin (-ix)}{-ix}\right)^2=\frac{\sinh^2 x}{x^2}$$

With these, the result is obvious.

I'm sorry, I know this is a bit overpowering of a formula to use on this question, but I thought it was worth noting.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.